An Analytical Account on Identity Formation and Agency :Exploring Female Characters in Alice Walker's The Color Purple - NEHAILI, Djihan Assala; SERKHAD, Noura; SELET ,Djihad Afaf (University of Ammar Theledji -Laghouat, 2021)
The present dissertation seeks to investigate the identity formation and agency among the female characters in Alice Walker’s novel The Color Purple (1982) . It aims at showcasing the intrinsic role that feminist solidarity plays in sustaining the female identity and self fulfillment in male-centred societies . The present work , also , endeavours to conduct a feminist as well as psychological study of the main five female characters : Celie , Shug , Sofia , Mary and Nettie in order to elucidate their ability to surmount the hindrances imposed on them because of their gender . In order to realize the objectives of the present study , a descriptive method along with an analytical one have been followed in order to draw a parallel link between feminist as well psychological analysis of female’s struggle in patriarchal societies . Finally , the present dissertation concludes that the female characters succeed in reconstructing their identities and maintain their agency because of their feminist bonding